What did older adults die from in Ecuador between 1990 and 2014? An analysis of mortality rates in later adulthood and senescence from preventable causes according to natural regions. - Buitrón-Andrade, Luis (2023)
Introduction: Globally, changes in the demographic structure are marking a trend towards aging in the population. United Nations projections establish that the number of older people between 1950 and 2000 increased by more than 141%. The elderly population often dies from avoidable causes. The present study shows the mortality rates from preventable causes between later adulthood and old age in the four natural regions that constitute the country. Material and methods: In order to compare the mortality rates per one hundred thousand inhabitants due to avoidable causes and by natural regions in Ecuador between 1990 and 2014 between later adulthood and senescence, we performed an exploratory ecological study based on the data acquired from official institutions of Ecuador. Results: The mortality rate in later adulthood (between 60 and 74 years of age) went from 410.84 in 1990 to 429.8 in 2014 per one hundred thousand inhabitants, while in senescence individuals older than 75 years), the rate was 8,845.94 in 1990 and 6,861.79 in 2014. The highest rates of mortality for preventable causes with early diagnosis and treatment were observed in senescence, followed by preventable causes with mixed measures, avoidable ones with sanitation measures, and avoidable with vaccination and preventive treatment (p<0.01). Mortality rates in older age were the country, compared to mortality rates in later adulthood (p<0.01). Conclusions: Mortality rates in the four natural regions of the country were higher during older age than in later adulthood due to different preventable causes, mainly related to early diagnosis and treatment.